2013
DOI: 10.1007/s10388-013-0382-8
|View full text |Cite
|
Sign up to set email alerts
|

A case report of pulmonary tumor thrombotic microangiopathy (PTTM) caused by esophageal squamous cell carcinoma

Abstract: A 67-year-old male was referred to our hospital after being diagnosed with esophageal squamous cell carcinoma of the middle thoracic esophagus. The clinical stage was T1b(sm)N4M1 cStage IVb, so he was admitted to our hospital for systemic chemotherapy. He had sustained fever and a dry cough. Chest computed tomography showed the presence of irregular shadows, and unidentified respiratory insufficiency had progressed. A transbronchial lung biopsy revealed a pulmonary artery tumor embolus of esophageal squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Fujishiro et al reported 103 patients with PTTM, among whom the most frequent primary cancer was gastric (58 cases), followed by lung (10 cases), breast (7 cases), cancer of unknown primary (f5 cases), ovarian (5 cases) and bladder (4 cases). 2 As shown in table 1, imatinib was effective in three cases of signet-ring cell carcinoma, including our case, but was weaker in cases of colon (patient 2) and breast (patients 4 and 5) cancer. The mechanism is still unclear, but it has been suggested that production of growth factors, including PDGF, might be different depending on the tumour characteristics.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Fujishiro et al reported 103 patients with PTTM, among whom the most frequent primary cancer was gastric (58 cases), followed by lung (10 cases), breast (7 cases), cancer of unknown primary (f5 cases), ovarian (5 cases) and bladder (4 cases). 2 As shown in table 1, imatinib was effective in three cases of signet-ring cell carcinoma, including our case, but was weaker in cases of colon (patient 2) and breast (patients 4 and 5) cancer. The mechanism is still unclear, but it has been suggested that production of growth factors, including PDGF, might be different depending on the tumour characteristics.…”
Section: Discussionsupporting
confidence: 54%
“…1 In fact, it has been reported that only 7 of 103 patients were pathologically diagnosed with PTTM while still alive. 2 Platelet-derived growth factor (PDGF) stimulation has been reported to be involved in the proliferation and anti-apoptosis of pulmonary artery endothelial cells and smooth muscle cells in patients with pulmonary hypertension (PH). [3][4][5] PDGF is also involved in the progression of PTTM.…”
Section: Introductionmentioning
confidence: 99%
“…A study has estimated the median survival as 5 days from admission to hospital 6. PTTM may be identified using video‐assisted thoracoscopic surgery, trans‐bronchial biopsy, right heart catheterization, and CT‐guided biopsy 7…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases exist in the literature of patients with PTTM diagnosed prior to death (8)(9)(10)(11)(12). Miyano et al reported a patient with previously resected gastric cancer in whom PTTM was suggested by elevated serum VEGF and D-dimer levels (8).…”
Section: Discussionmentioning
confidence: 99%